Coordination and Hydroboration of Ru(II)‐Borate Complexes: Dihydridoborate vs. Bis(dihydridoborate). Issue 18 (8th March 2022) - Pathak, Kriti; Gayen, Sourav; Saha, Suvam; Nandi, Chandan; Mishra, Shivankan; Ghosh, Sundargopal
Abstract: Treatment of [Cp*RuCl2 ]2, 1, [(COD)IrCl]2, 2 or [( p ‐cymene)RuCl2 ]2, 3 (Cp*= η 5 ‐C5 Me5, COD = 1, 5‐cyclooctadiene and p ‐cymene= η 6 ‐ i PrC6 H4 Me) with heterocyclic borate ligands [Na[(H3 B)L], L1 and L2 (L1 : L=amt, L2 : L=mp; amt=2‐amino‐5‐mercapto‐1, 3, 4‐thiadiazole, mp=2‐mercaptopyridine) led to the formation of borate complexes having uncommon coordination. For example, complexes 1 and 2 on reaction with L1 and L2 afforded dihydridoborate species [L A M( μ ‐H)2 BHL] 4 –6 (4 : L A =Cp*, M=Ru, L=amt; 5 : L A =Cp*, M=Ru, L=mp; 6 : L A =COD, M=Ir, L=mp). On the other hand, treatment of 3 with L2 yielded cis‐ and trans‐ bis(dihydridoborate) species, [Ru{( μ ‐H)2 BH(mp)}2 ], cis ‐7 and trans ‐7 . The isolation and structural characterization of fac‐ and mer‐ [Ru{( μ ‐H)2 BH(mp)}{( μ ‐H)BH(mp)2 }], 8 from the same reaction offered an insight into the behaviour of these dihydridoborate species in solution. Fascinatingly, despite having reduced natural charges on Ru centres both at cis ‐and trans‐ 7, they underwent hydroboration reaction with alkynes that yielded both Markovnikov and anti‐Markovnikov addition products, 10 a –d . Abstract : New 18‐electron pseudo‐octahedral Ru‐dihydridoborate and bis(dihydridoborate) complexes have been synthesized and structurally characterised. Isolation of Ru‐bis(dihydridoborate) complexes permitted hydroboration reactions with [HC≡C(CO2 Me)] that unusually led to the formation of η 4 ‐ σ, π ‐alkene‐borane complexes via both Markovnikov and anti‐Markovnikov additions.